Influence of elevated temperature on properties of lightweight concrete containing palm oil fuel ash (POFA) subjected to water cooling - Nur Arifah Najihah, Arifen (2018)
Lightweight concrete has been largely used as construction material for development. The cement production produce carbon dioxide gas which harmful to the environment. At the same time, Malaysia being one of the largest producer and exporter palm oil produces POFA which disposed as waste. Thus, this research investigate the influence of elevated temperature on properties of lightweight concrete containing palm oil fuel ash (POFA) as partial cement replacement. Lightweight concrete was partially replaced by different percentages of POFA (10%, 20%, 30% and 40%). Compressive strength test was conducted on control specimens as well as the specimens after cooling method. Then, the specimens were subjected to high temperature beginning from 200°C, 400°C, 600°C until 800°C in electric furnace for 1 hour period. After that, the concrete specimens subjected to water cooling until there is no steam out. Next, the specimens were observed for its physical changes namely color, weight loss and cracks. The residual compressive strength also been tested. At 40% of POFA, the weight loss is the highest at all temperatures due to the greater moisture content control by the high volume of POFA. Next, the residual compressive strength at 10% of POFA show the highest value because of the concrete undergo two types of process name hydration process and pozzolanic reaction which more calcium silicate hydrate (C-S-H) gel produced. In addition, the hairline cracks were observed at 400°C and more cracks can be seen at 600°C-800°C.